KEDUDUKAN DAN KONTRIBUSI HUKUM ISLAM TERHADAP HUKUM NASIONAL DALAM BIDANG MU’AMALAT - Ruwainta Samniah; Akhmad Khisni (UNISSULA Semarang, 2018)
The position of Islamic law is something that is taken into account in Indonesia because of its contribution to the development of national law. One of the doors to the contribution of Islamic law in national law is through Jurisprudence which is another instrument in the formation of the law, which in the legislation of the Supreme Court, requires the judge to find the right law in determining the decision. In this case the judge may use the Islamic legal norms which are deemed to be able to find a sense of justice for the justice seeker. About one of the objects of Islamic law in the field of muamalah which contains the norms of Islamic law in positive law. With this the title of Position and Contribution of Islamic law to the national law in the field of Mu'amalat, which will be discussed in this journal.The purpose of this paper so that more attention again for the future to think about the more contribution leads to the role of Islamic law in influencing the contents of national law. The method used in this study is Juridical Normative with data collection methods used is study of the study of a series of studies by reviewing the theories, opinions, and the main ideas in print media.Keywords: Position, Contribution, Islamic Law, National Law, Mu'amalat.